The importance of pharmaceutical performance in orientation and reception to HIV patients: can we make a difference? (Research, Society and Development, 2020)
The objective of this work was to carry out a bibliographic review highlighting the social importance of the pharmaceutical professional in welcoming and guiding people living with HIV / AIDS (PLHIV). This is a narrative-type bibliographic review, which included articles, monographs, dissertations and theses published during the years 2007 to 2020. It is possible to verify that the reception provides a closer contact between pharmacists and PLHIV. In this way, it can directly contribute to improvements in terms of adherence and effectiveness of pharmacotherapy, observed from the decrease in viral load, hospitalizations, medical care and exams. In addition, there is a reduction in complications inherent to HIV, such as the incidence of opportunistic diseases that can lead those affected to hospitalizations and death. Thus, the pharmacist who receives and advises patients with HIV has proved to be a key part in adhering to treatment, improving health and reducing costs for the Sistema Único de Saúde.